Closer ties between Malaysia-Bosnia following MoU signed by UMP and MBTCA - UMP, PNC (2019)
Universiti Malaysia Pahang (UMP) signed a Memorandum of Understanding (MoU) with Malaysia Bosnia Trade Cooperation Association (MBTCA) that would pave the way for collaborations in the fields of engineering and technology with universities in Bosnia.